Safflower root and shoot growth affected by soil compaction - Mansano Sarto, Marcos Vinicius [UNESP]; Bassegio, Doglas [UNESP]; Rosolem, Ciro Antonio [UNESP]; Wobeto Sarto, Jaqueline Rocha [UNESP] (Inst Agronomico, 2018)
Safflower (Carthamus tinctorius L.1 is a commercial seed crop grown for its good yield of high-quality oil, It is tolerant to water stress but may be sensitive to soil compaction. The aim of this study was to assess safflower growth under different degrees of soil compaction at depths of 0.15 m to 0.20 tn. The experiment was carried out in PVC pots constructed from three rings. Five levels of penetration resistance (0.20, 0.33, 0.50, 0.93, and 1.77 MPal were applied in the intermediate ring, and two safflower genotypes, IMA-4904 and IMA-2106, were examined, There was no difference between safflower genotypes with respect to their resistance to soil compaction, which reduced root length density in the compacted layer and changed the root distribution in the soil profile, but did not prevent the moots from crossing the compacted layer and developing in depth. Increased soil bulk density in the compacted layer increased root diameter of the IMA-7106 genotype. Penetration resistance levels over 020 MPa (density of 1.2 ing.dm) limited safflower root development. The maximum safflower growth occurred when the soil penetration resistance was 0.86 MPa, In this study, the Q1/2 index was higher than 1.77 and 1.55 for the IMA-2106 and IMA-4904 genotypes, respectively, Hence, safflower has proven to be tolerant to soil compaction, and stands out as a species with potential to decrease soil bulk density,
Keywords: Carthomustinctorius L.; root length; bulk density; penetration resistance